(untitled) (Editora Impacto Científico, 2025)
Active practices in Education need to be reflective and primarily involve an isolated compression of the concepts of Active School, Active Methodology and Active Learning, as well as the way in which these three important educational elements interact in the teaching and learning process, enhancing pedagogical practices, among which is the Active Methodology “Peer Instruction”, the central topic of this article. In this way, the present work aims to understand the interactivity of these educational elements after understanding the separate concepts, to then reflect the application of “Peer Instruction” in face-to-face and online classes, given that the modality has flexibility for wide application, considering that technological resources are essential for developing projects in all professional areas. For development, a qualitative bibliographical research was carried out on some academic materials. In the end, it was concluded that the Active Methodology “Peer Instruction” consists of an effective tool that can add to pedagogical resources through the integrated participation of the student.